Strength of materials - Sandor, Bela Imre (Prentice Hall, 1978)
This material is presented in starred sections (which may be omitted on a first reading without interrupting the flow of the presentation) and includes a full treatment of the Mohr circle and its application to the determination of moments of inertia and strains as well as stresses; a lucid elementary presentation of the theory of the center of shear; and one of the few elementary presentations of the theory of the center of shear; and one of the few elementary discussions of the "Myosotis" method of calculating beam deflections, a method which often possesses considerable advantages over the more usual methods involving moment-area or the differential equation of bending.